Model Pertumbuhan Ekonomi Dengan Pendekatan Vector Error Correction Model di Provinsi Jawa Barat Tahun 2018-2022 - Susilo, Joko Hadi; Laila, Agustina Naviatur Nurul; Alfiyana, Siti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to determine and analyze economic growth in West Java Province. In addition, it also analyzes the effect of poverty, poverty rate and minimum wage on economic growth in 2018-2022. This type of research is conducted with a quantitative approach. Secondary data sources with data collection through literature studies and the official website of the West Java Province BPS. This study uses the Vector Error Correction Model (VECM) method. The sampling technique uses purposive sampling, with a total sample of 135 samples from 27 districts/cities in West Java Province. Based on the results of the short-term analysis, the poverty variable has a significant negative effect on economic growth. Then the poverty and minimum wage variables do not affect the economic growth variable. Furthermore, in the long term all variables, namely poverty, poverty rate and minimum wage have a significant negative effect on economic growth.